Signifikansi Funding Agencies pada Global Research Council (GRC) Sebagai Bagian Masyarakat Sipil Global - Renatha Ayu Rossdiana (AEGIS : Journal of International Relations, 2022)
AbstractThe paper discusses the question of the significance of the role of funding agencies in the Global Research Council (GRC). GRC, part of the Global Civil Society (GCS) as an epistemic community, is a virtual organization formed in 2012. Most of its members are from funding agencies and aim to distribute knowledge. This paper concludes that funding agencies at GRC are critical masses that are important in bridging interests between scientific entities in funding research on a global scale and creating a better assessment of research funding. These two things are the difference between other knowledge networks. Conceptually, the author explains the position of GRC as part of global civil society in the form of Global Knowledge Networks (KNETs) and uses the Critical Mass conception in Science, Technology, and Innovation (STI). The author conducted participant observation to be involved in GRC and collected secondary data from journals, books and other related sources. The author elaborates on the mutually influencing relationship between funding agencies and GRC by using several examples of funding cases and best practices from GRC's influence on these funding agencies and how funding agencies affect global funding through GRC. Keywords: Epistemic Community, Global Civil Society, KNETs, Critical Mass, GRC, Funding Agencies